2019
DOI: 10.1016/j.jocn.2019.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar interbody fusion rates with 3D-printed lamellar titanium cages using a silicate-substituted calcium phosphate bone graft

Abstract: a b s t r a c tThe synthetic bone graft material, silicate-substituted calcium phosphate (SiCaP), has been successfully used in spinal fusion surgery. The efficacy of SiCaP-packed 3D-printed lamellar titanium cages used in transforaminal lumbar interbody fusion (TLIF) and lateral lumbar interbody fusion (LLIF) requires investigation. This study evaluated the efficacy of this combination in TLIF and LLIF surgeries treating adult spinal deformities and degenerative disorders. We retrospectively analysed a consec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Titanium alloy (Ti6Al4V) was the material used to manufacture the spinal implants by 3DP (22/23 studies, 191 patients) in all but one study (Amelot et al [27]), which used PolyEther-Ketone-Ketone, or PEKK, implants for six patients. PS implant designs were used in 21 of 23 reviewed articles (5 case series, 14 case reports; 64 patients), whereas two case series [28,29] and a case report [30], respectively, were published on a generic (OTS) devices (135 patients), the Medussa-PL [29], K2M Lamellar Titanium Cage [28] and EIT Cellular Titanium interbody cage [30]. Thayaparan et al [30] implanted both PS and OTS 3DP devices.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Titanium alloy (Ti6Al4V) was the material used to manufacture the spinal implants by 3DP (22/23 studies, 191 patients) in all but one study (Amelot et al [27]), which used PolyEther-Ketone-Ketone, or PEKK, implants for six patients. PS implant designs were used in 21 of 23 reviewed articles (5 case series, 14 case reports; 64 patients), whereas two case series [28,29] and a case report [30], respectively, were published on a generic (OTS) devices (135 patients), the Medussa-PL [29], K2M Lamellar Titanium Cage [28] and EIT Cellular Titanium interbody cage [30]. Thayaparan et al [30] implanted both PS and OTS 3DP devices.…”
Section: Resultsmentioning
confidence: 99%
“…The application of custom-designed implants was categorised into pedicle fixation rod (1 patient) [30], posterior arthrodesis cage (2 papers, 4 patients) [41,45], interbody fusion cage (5 papers, 5 patients) [34,[37][38][39]42], vertebral body replacement device (11 papers, 42 patients) [25-27, 34-36, 40, 43, 44, 46, 47] and miscellaneous sacral reconstructive device (3 papers, 12 patients) [31][32][33]. Utilisation of OTS devices manufactured using 3DP was limited to interbody fusion cages for degenerative pathology in the lumbar (3 papers, 134 patients) [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much like other spinal surgeries, spinal fusion is a procedure that has shown promise in utilizing 3DP fusion cages for improved surgical outcomes in both single- and multi-level fusions. In a retrospective analysis completed by Mokawem et al [ 26 ] in the UK, a consecutive series of 93 patients with lumbar degenerative disease or deformity requiring interbody fusion cages underwent transforaminal lumbar interbody fusion or lateral lumbar interbody fusion with silicate-substituted calcium phosphate-packed 3DP lamellar titanium cages printed from 3D reconstructions of CT images of each patient. After evaluating the solidity of fusion 12 months after surgery and concurrently administering surveys assessing patient quality-of-life, pain, and level of disability, the authors demonstrated excellent fusion success in 92 of the 93 patients (98.9% success rate), as well as significantly improved patient-reported outcomes/satisfaction, demonstrating superb success with this 3DP fusion cage approach.…”
Section: Applications For 3dp In Spine Surgerymentioning
confidence: 99%
“…Some groups have designed 3D-printed titanium cages with internal architecture that optimizes mechanical properties, osteoblast activity, and bony ingrowth. 57,58 These 3D-printed structures may have the potential to obviate the need for additional packing of ceramictype materials. Additive manufacturing provides an efficient means to control the microarchitecture, and subsequently, the biologic activity of a specific material.…”
Section: Future Directions: 3d-printed Composite Materialsmentioning
confidence: 99%